Factors Associated with Self-Reported Drug Allergies in a Large Chronic Spontaneous Urticaria Cohort - Rauscher, Christine; Petrov, Andrej A.; Fajt, Merritt L. (Current Drug Safety, 2021)
Introduction: Chronic spontaneous urticaria (CSU) is characterized by recurrent hives without a known trigger. While certain drugs are associated with urticaria exacerbations, the overall drug allergy incidence in CSU is unknown. We hypothesized that the incidence of drug allergy in CSU would be greater than the general population and that there would be distinguishing clinical features of drug-allergic CSU patients. Methods: 362 adult CSU patients seen over a 10-year period at a University Allergy/Asthma clinic were identified. Patients reported no drug allergies or any drug allergy. Multiple drug allergies were defined as allergies to ≥ 2 chemically unrelated drugs. Using Chi-square or Wilcoxon analysis, we compared demographic features of CSU with and without drug allergy and with multiple vs. single drug allergy. Results and Discussion: Overall, 202 CSU patients (56%) reported drug allergy. Drug allergic CSU patients were older, with a greater proportion of whites and higher BMI vs. CSU without drug allergy (p=0.002, p=0.047, p=0.004, respectively). Penicillin was the most common drug allergy, with urticaria the most frequently reported reaction. Female sex, white race, older age at the visit, and co-existing asthma were more common in multiple drug allergy (n=115) vs. single drug allergy (p=0.002, p=0.02, p=0.03, p=0.0002, respectively). Conclusion: In CSU, the prevalence of self-reported drug allergies was higher than the general population. Drug allergy is associated with older age, white race and higher BMI, while multiple drug allergy was also associated with asthma. These CSU sub-populations should be studied to avoid the potential for morbidity associated with less efficacious and more costly drugs.
Keywords: angioedema